1
$\begingroup$

Namely, when does the polynomial $z^2 + a z + b = 0$ with $a,b \in \mathbb{C}$ have both roots in the left half complex?

As the sum of the roots $z_1 + z_2 = -a$, it follows that if $\Re a < 0$ then one of $\Re z_1$ or $\Re z_2$ must be positive. So a necessary condition is $\Re a > 0$. What is a sufficient condition? (Please provide a proof for it)

Edit: We can modify the answer below for the "more general case". A necessary and sufficient condition for the roots of $$ A z^2 + B z + C = 0$$ with $A>0$, $B,C \in \mathbb{C}$ to lie on the left complex half plane, i.e. $\Re z_i < 0$, is to have $$\sqrt{2} \Re(B) > \sqrt{\Re(B^2 - 4AC) + \vert B^2 - 4AC \vert}.$$ If we let $B = B_1 + i B_2$, $C = C_1 + i C_2$, with $B_i, C_i \in \mathbb{R}$ then the above condition can also be written as $$ B_1 > 0, \qquad B_1^2 C_1 + B_1 B_2 C_2 - A C_2^2 > 0. $$

$\endgroup$
  • $\begingroup$ I added the "complex-numbers" tag to your post. Cheers! $\endgroup$ – Robert Lewis Oct 8 '18 at 19:53
  • $\begingroup$ What you are asking is a special case of the Routh-Hurwitz theorem. It should be possible, however, to give a simple answer in this special case. $\endgroup$ – Helmut Oct 8 '18 at 20:20
  • $\begingroup$ Routh-Hurwitz seems to be working only when all the coefficients are real and have the same sign. $\endgroup$ – pitonist Oct 9 '18 at 4:30
2
+50
$\begingroup$

Let us separate it into two cases :

Case 1 : When $\Re(a^2-4b)+|a^2-4b|=0$, i.e. $\Re(a^2-4b)\le 0$ and $\Im(a^2-4b)=0$, the roots of $z^2+az+b=0$ are given by $$z_1,z_2=\frac{-(\Re(a)+i\Im(a))\pm i\sqrt{4b-a^2}}{2}$$ from which $$\Re(z_1)\lt 0\quad\text{and}\quad \Re(z_2)\lt 0\iff -\frac{\Re(a)}2\lt 0\iff \Re(a)\gt 0$$follows.

Case 2 : When $\Re(a^2-4b)+|a^2-4b|\not=0$, let us use the following lemma (the proof for the lemma is written at the end of the answer) :

Lemma : Let $\Delta :=t^2-4su$. If $s\not=0$ and $\Re(\Delta)+|\Delta|\not=0$, then the roots of $$sx^2+tx+u=0$$ are given by $$x=-\frac{t}{2s}\pm\frac{\Delta+|\Delta|}{2\sqrt 2\ s\sqrt{\Re(\Delta)+|\Delta|}},$$ i.e. $$x=-\frac{t}{2s}\pm \left(\frac{\sqrt{\Re(\Delta)+|\Delta|}}{2\sqrt 2\ s}+i\frac{\Im(\Delta)}{2\sqrt 2\ s\sqrt{\Re(\Delta)+|\Delta|}}\right)$$

From the lemma, the roots of $z^2+az+b=0$ are given by $$\small z_1,z_2=-\frac{\Re(a)+i\Im(a)}{2}\pm\left(\frac{\sqrt{\Re(a^2-4b)+|a^2-4b|}}{2\sqrt 2}+i\frac{\Im(a^2-4b)}{2\sqrt 2\sqrt{\Re(a^2-4b)+|a^2-4b|}}\right)$$ from which $$\begin{align}&\Re(z_1)\lt 0\qquad\text{and}\qquad \Re(z_2)\lt 0 \\\\&\small\iff -\frac{\Re(a)}{2}+\frac{\sqrt{\Re(a^2-4b)+|a^2-4b|}}{2\sqrt 2}\lt 0\quad\text{and}\quad -\frac{\Re(a)}{2}-\frac{\sqrt{\Re(a^2-4b)+|a^2-4b|}}{2\sqrt 2}\lt 0 \\\\&\iff \frac{\Re(a)}{2}\gt \frac{\sqrt{\Re(a^2-4b)+|a^2-4b|}}{2\sqrt 2} \\\\&\iff \sqrt 2\ \Re(a)\gt \sqrt{\Re(a^2-4b)+|a^2-4b|} \\\\&\iff \Re(a)\gt 0\qquad \text{and}\qquad 2(\Re(a))^2\gt \Re(a^2-4b)+|a^2-4b|\end{align}$$ follows.

From the two cases, a necessary and sufficient condition is $$\color{red}{\Re(a)\gt 0\qquad \text{and}\qquad 2(\Re(a))^2\gt \Re(a^2-4b)+|a^2-4b|}$$


Finally, let us prove the lemma.

Proof for the lemma :

We get $$\begin{align}&s\left(-\frac{t}{2s}\pm\frac{\Delta+|\Delta|}{2\sqrt 2\ s\sqrt{\Re(\Delta)+|\Delta|}}\right)^2+t\left(-\frac{t}{2s}\pm\frac{\Delta+|\Delta|}{2\sqrt 2\ s\sqrt{\Re(\Delta)+|\Delta|}}\right)+u \\\\&=s\left(\frac{t^2}{4s^2}\mp\frac{t(\Delta+|\Delta|)}{2\sqrt 2\ s^2\sqrt{\Re(\Delta)+|\Delta|}}+\frac{(\Delta+|\Delta|)^2}{8s^2(\Re(\Delta)+|\Delta|)}\right) \\\\&\qquad\qquad\qquad\qquad -\frac{t^2}{2s}\pm\frac{t(\Delta+|\Delta|)}{2\sqrt 2\ s\sqrt{\Re(\Delta)+|\Delta|}}+u \\\\&=\frac{t^2}{4s}\mp\frac{t(\Delta+|\Delta|)}{2\sqrt 2\ s\sqrt{\Re(\Delta)+|\Delta|}}+\frac{(\Delta+|\Delta|)^2}{8s(\Re(\Delta)+|\Delta|)}\\\\&\qquad\qquad\qquad\qquad -\frac{t^2}{2s}\pm\frac{t(\Delta+|\Delta|)}{2\sqrt 2\ s\sqrt{\Re(\Delta)+|\Delta|}}+u \\\\&=\frac{-\Delta}{4s}+\frac{(\Delta+|\Delta|)^2}{8s(\Re(\Delta)+|\Delta|)} \\\\&=\frac{-(\Delta+\overline{\Delta})\Delta+\Delta^2+\Delta\overline{\Delta}}{8s(\Re(\Delta)+|\Delta|)} \\\\&=0\qquad\quad\square\end{align}$$

$\endgroup$
1
$\begingroup$

If

$\mu_1, \mu_2 \in \Bbb C \tag 1$

are the roots of

$z^2 + az + b = 0, \; a, b \in \Bbb C, \tag 2$

then they satisfy the quadratic formula,

$\mu_1, \mu_2 = \dfrac{-a \pm \sqrt{a^2 - 4b}}{2}, \tag 3$

provided we take some care in the interpretation of $\sqrt{\cdot}$; since in general $b^2 - 4a \in \Bbb C \setminus \Bbb R$, we must carefully specify just what we intend

$\theta = \arg{\sqrt{a^2 - 4b}} \in [0, 2\pi) \tag 4$

to be; I think the most generally accepted convention, assuming $a^2 - 4b \ne 0$, is to write

$a^2 - 4b = \vert a^2 - 4b \vert e^{i \arg(a^2 - 4b)}, \tag 5$

and then choose (or, define)

$\sqrt{a^2 - 4b} = \sqrt{\vert a^2 - 4b \vert} e^{i \arg(a^4 - 4b) / 2}; \tag 6$

we check:

$(\sqrt{\vert a^2 - 4b \vert} e^{i \arg(a^2 - 4b) / 2})^2 = (\sqrt{ \vert a^2 - 4b \vert })^2 (e^{i \arg(a^4 - 4b) / 2})^2$ $= \vert a^2 - 4b \vert e^{2i\arg((a^2 - 4b) / 2)} = \vert a^2 - 4b \vert e^{i\arg(a^2 - 4b)} = a^2 - 4b; \tag 7$

of course with (6) in place, we also see that

$(-\sqrt{a^2 - 4b})^2 = a^2 - 4b \tag 8$

as well; and of course, (3) is a necessary for $\mu_1$, $\mu_2$ to satisfy (2), since it follows from completing the square: from (2),

$z^2 + az = -b, \tag 9$

$\left (z + \dfrac{a}{2} \right )^2 = z^2 + az + \dfrac{a^2}{4} = \dfrac{a^2}{4} - b = \dfrac{1}{4}(a^2 - 4b), \tag{10}$

whence

$z + \dfrac{a}{2} = \pm \dfrac{1}{2}\sqrt{a^2 - 4b} \iff \mu_1, \mu_2 = z = \dfrac{-a \pm \sqrt{a^2 - 4b}}{2}. \tag{11}$

It should be noted here that

$a^2 - 4b = 0 \Longrightarrow \mu_1 = \mu_2 = -\dfrac{1}{2}a, \tag{11.5}$

that is, we obtain a double real root. Bearing this in mind as having resolved the case $a^2 - 4b = 0$, we proceed under our hypothesis $a^2 - 4b \ne 0$.

With (6) in place we may write a precise expression for the real parts of the roots of (2) via (3): we have

$a = \Re(a) + i \Im(a), \tag{12}$

and

$\sqrt{a^2 - 4b} = \sqrt{\vert a^2 - 4b \vert} e^{i \arg(a^2 - 4b) / 2}$ $= \sqrt{\vert a^2 - 4b \vert} \cos \dfrac{ \arg (a^2 - 4b)}{2} + i \sqrt{\vert a^2 - 4b \vert} \sin \dfrac{ \arg (a^2 - 4b)}{2}; \tag{13}$

it now follows from (3), (11) that the real parts of $\mu_1$ and $\mu_2$ are

$\Re(\mu_1), \; \Re(\mu_2) = \dfrac{1}{2}\left (-\Re(a) \pm \sqrt{\vert a^2 - 4b \vert} \cos \dfrac{ \arg (a^2 - 4b)}{2} \right ); \tag{14}$

we can in principle, from (14), determine the relationship(s) $a$ and $b$ must satisfy in order that

$\Re(\mu_1), \; \Re(\mu_2) < 0; \tag{15}$

indeed,

$\Re(\mu_1), \Re(\mu_2) = \dfrac{1}{2}\left (-\Re(a) \pm \sqrt{\vert a^2 - 4b \vert} \cos \dfrac{ \arg (a^2 - 4b)}{2} \right ) < 0$ $\iff -\Re(a) + \left \vert \sqrt{\vert a^2 - 4b \vert} \cos \dfrac{ \arg (a^2 - 4b)}{2} \right \vert < 0, \tag{16}$

which logical equivalence ($\Longleftrightarrow$) binds since

$\pm \sqrt{\vert a^2 - 4b \vert} \cos \dfrac{ \arg (a^2 - 4b)}{2} = \left \vert \sqrt{\vert a^2 - 4b \vert} \cos \dfrac{ \arg (a^2 - 4b)}{2} \right \vert \tag{17}$

for at least one choice of $+/-$ in the "$\pm$" sign.

(16) is in fact completely determinative of (15), since it affirms that the largest of the two $\Re(\mu_1)$, $\Re(\mu_2)$ is negative.

A few words on the special case with both $a, b \in \Bbb R$, that is,

$a = \Re(a), b = \Re(b) \in \Bbb R, \tag{18}$

we have

$\arg(a^2 - 4b) = 0, \pi \Longleftrightarrow \dfrac{ \arg (a^2 - 4b)}{2} = 0, \dfrac{\pi}{2} \Longrightarrow \cos \dfrac{ \arg (a^2 - 4b)}{2} = 1, 0; \tag{19}$

with $\cos (\arg(a^2 - 4b) / 2) = 1$ we find that

$ \left \vert \sqrt{\vert a^2 - 4b \vert} \cos \arg \dfrac{(a^2 - 4b)}{2} \right \vert = \sqrt{\vert a^2 - 4b} \vert, \tag{20}$

and so, via (14), (18)

$\mu_1 = \Re(\mu_1), \; \mu_2 = \Re(\mu_2) = \dfrac{1}{2}\left (-a \pm \sqrt{\vert a^2 - 4b \vert} \right ); \tag{21}$

in such a situation we thus see that both roots $\mu_1$ and $\mu_2$ have negative real part when

$a = \vert a \vert > \sqrt{\vert a^2 - 4b \vert}, \tag{22}$

that is, when

$0 < a, \; 0 < b < \dfrac{a^2}{2}; \tag{23}$

on the other hand, with $\cos (\arg(a^2 - 4b) / 2) = 0$, it is even easier to realize that we must have, again with the aid of (14),

$\Re(\mu_1) = \Re(\mu_2) = -\dfrac{1}{2} \Re(a), \tag{24}$

and $\mu_1, \mu_2 = \bar \mu_1$ are a complex conjugate pair; this is consistent with (13), which in the present instance reverts to

$\sqrt{a^2 - 4b} = i \sqrt{\vert a^2 - 4b \vert}, \tag{24}$

and then (11) yields

$\mu_1, \mu_2 = \dfrac{-a \pm i\sqrt{\vert a^2 - 4b \vert}}{2}. \tag{25}$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.